A Comparison of Antimicrobial usage in ICUs and Wards of a Private Tertiary Care Hospital: A Prospective Study - Rani, Prity; Tiwari, Pramil; Sharma, Vidushi (Indian Journal of Pharmacy Practice)
Introduction: Appropriate use of antimicrobials is the best possible way to safeguard the effectiveness of existing antimicrobials and to reduce the development of antimicrobial resistance. Objective: This study aims to evaluate and compare the utilization pattern of antimicrobial drugs in intensive care units (ICUs) and wards of a private tertiary care hospital. Materials and Methods: This is an observational prospective study carried out in ICUs and wards of private tertiary care hospital. In-patients receiving at least one antimicrobial agent were included in the study while patients with incomplete information were excluded out of the study. Utilization pattern of antimicrobial drugs was analyzed using RPM plus indicators recommended by World Health Organization. Student’s t-test was used to determine statistical difference between continuous variables of ICUs and wards. Results: The number of patients studied in ICUs and wards was 405 and 561, respectively. In ICUs, the average number of medications prescribed was 13.49±1.41, of which average number of AMDs was 2.49±1.61. While in wards, the average number of medication was 10.51±5.17, of which average number of AMDs was 1.91±1.27. Overall 75% antimicrobials were administered by parenteral route. Conclusion: The findings of this study indicate that there is scope of improvement in extent of use of parenteral antimicrobial therapy.
Keywords: Antimicrobials; Antimicrobial resistance; Antimicrobial sensitivity test; Intensive care unit; Antimicrobial drug utilization; Prescribing pattern.